Comment: Population Programs and Fertility - Rosero Bixby, Luis (2001)
Understanding the rationale and sources of support for population programs is crucial for assessing their impact and chances of survival. One of the most notable features of population agencies and programs is that not long ago—in the 1950s—they were unthinkable. "To govern is to populate" was the unquestioned principle of good government attributed to Juan Bautista Alberdi, the nineteenth-century statesman and philosopher from Argentina. How did governments come to abandon this principle and establish birth control programs (later called euphemistically "family planning" and "reproductive health" programs)? The answer "rapid population growth" or "high demographic density" may seem obvious to demographers but it is not so obvious for politicians, especially considering the opposition to birth control by religious authorities and other powerful interest groups and the nationalist pride associated with large populations.